Diversity of Natural Enemies in Organic Cauliflower, Brassica oleracea var. Botrytis Applied with Biopesticides from Plant Extracts - Tuan, Leah C. (International Journal of Environment, Agriculture and Biotechnology, 2019)
Selected botanicals used as foliar bio pesticide as a sustainable approach on insect pest management for cauliflower production was studied for three months at the University Demo Farm, University of Eastern Philippines, Main Campus, University Town, Catarman, Northern Samar to determine their effect on the incidence of natural enemies on cauliflower. Presence of natural enemies at the experimental area was not significantly influenced by the introduction of the bio pesticide. Abnormalities in the environmental condition during the conduct of the experiment was the major contributory factor to its effectiveness. Yet, repellant and antifeedant properties of the bio pesticide must have prevented the establishment of pest species. The prevalence of natural enemies and other arthropods in the area is a clear indicator of a clean and safe environment.